Predator Field and Colony Morphology Determine the Defensive Benefit of Colony Formation in Marine Phytoplankton - Ryderheim, Fredrik; Hansen, Per Juel; Kiørboe, Thomas (Frontiers in Marine Science, 2022)
Colony formation in marine phytoplankton can be modified by the presence of grazers, but the effect of colony size and shape on the feeding behavior of grazers is still relatively unknown. To explore the defensive role of colony formation, we examined the feeding response of three differently sized grazers (copepodites, copepod nauplii, and two heterotrophic dinoflagellates) feeding on colony-forming phytoplankton, using both direct video observations and bottle incubations. We found a dramatic increase in capture clearance rate with colony size for copepodites, up to 140% higher in the largest diatom chains relative to their solitary cells. This was in part facilitated by a mechanism – described here for the first time – by which copepods efficiently detect and capture colonies using the antennules, thereby increasing their capture radius. Prey handling time by copepodites increased with colony size, but did not limit prey ingestion. Larger chains of diatoms were efficiently handled and consumed by the copepodites, whereas larger spherical colonies of Phaeocystis globosa were rejected subsequent to capture. In contrast, colonial phytoplankton were better protected against the microzooplankton and copepod nauplii examined, since these only managed to consume smaller colonies equivalent of a few cells. We find that the defensive value of colony formation depends on the size and foraging behavior of the grazer and the size and shape of the colony. Thus, the defensive benefit is therefore a function of the composition of the grazer community. We argue that bloom formation in chain-forming diatoms is facilitated by the efficient protection against rapidly responding micro-grazers and the lagged numerical response of efficient copepod grazers.